2004
DOI: 10.1007/s00384-003-0556-2
|View full text |Cite
|
Sign up to set email alerts
|

Should we monitor vitamin B 12 levels in patients who have had end-ileostomy for inflammatory bowel disease?

Abstract: We do not recommend routine screening for vitamin B12 deficiency in this group of patients unless they have undergone additional small bowel resection or have ongoing small bowel inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…While several studies have reported low average vitamin B 12 levels in CD patients, others have found contradicting results. 3 5 10 11 12 13 14 15 In our study, the patients with CD had significantly lower levels of serum vitamin B 12 than the UC patients and controls, while the prevalence of vitamin B 12 deficiency was similar in the UC patients and controls. These results echoed those of previously reported studies about the prevalence of vitamin B 12 deficiency in patients with UC.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…While several studies have reported low average vitamin B 12 levels in CD patients, others have found contradicting results. 3 5 10 11 12 13 14 15 In our study, the patients with CD had significantly lower levels of serum vitamin B 12 than the UC patients and controls, while the prevalence of vitamin B 12 deficiency was similar in the UC patients and controls. These results echoed those of previously reported studies about the prevalence of vitamin B 12 deficiency in patients with UC.…”
Section: Discussionsupporting
confidence: 47%
“…While a number of previous studies indicated that CD patients tended to present vitamin B 12 deficiencies, others did not support this finding. 10 11 12 The reported prevalence of vitamin B 12 deficiency in patients with CD ranged from 5.6% to 38%. 13 Vitamin B 12 deficiency in IBD patients has multiple potential mechanisms, including inflammation of the distal ileum, the development of fistulas, small intestinal bacterial overgrowth, and resection of the distal ileum.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded this study based on our inclusion criteria (3). Jayaprakash et al reported their data without a healthy control group, and some of the patients they included had been receiving vitamin B12 supplementation [39]. We excluded this study based on our inclusion criteria (2) and (4).…”
Section: Discussionmentioning
confidence: 99%
“…Since ileostomies with resection of a large part of the terminal ileum were most frequent in the present series, the loss of vitamin B 12 (cobalamin) should also be considered [26] . Vitamin B 12 defi ciency is known to cause impaired myelinization and / or demyelization of neuronal cells [22] .…”
Section: Possible Causes For Diff Erences In Outcomesmentioning
confidence: 99%